Acute Coronary Syndrome Patients Admitted to Coronary Care Unit: An In-Hospital Outcome at King Abdulaziz University Hospital - Layth Mimish,; Mohamed Radwan, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The primary objective of this observational study is to compare clinical data and short-term outcome of patients admitted with acute coronary syndromes to coronary care unit in King Abdulaziz University Hospital over 1 year period, with patients enrolled in a multinational registry. The study cohort consisted of 399 patients hospitalized in King Abdulaziz University Hospital and 4,445 patients from the Global Registry of Acute Coronary Events. Average age of patients in King Abdulaziz University Hospital was nearly a decade younger (56 vs. 66 years), with male predominance (75% vs. 69%). Clinical presentation and management strategies were nearly the same, but in patients with ST elevation myocardial infarction, thrombolysis rather than primary percutaneous intervention was the main strategy in our group. In-hospital mortality rates were less in King Abdulaziz University Hospital patients (3% vs. 3.8%). This difference is probably related to smaller sample size, and late presentation. Future studies with larger sample size should explore the effects of differences in patient characteristics and treatment practices with long-term prognosis.